Haiti in Caribbean context : ethnicity, economy and revolt - Nicholls, David (St, Martin's Pr. New YorkUS, 1985)
Examines in historical perspective, connections between ethnic structures and the economy, showing how the phenomena of political domination and revolt are to be understood in the light of these connections.